Global Large Solution for the Tropical Climate Model Without Thermal Diffusion (Journal of Partial Differential Equations, 2025)
In this paper, we consider the Cauchy problem of $d$-dimensional $(d=2,3)$  tropical climate model without thermal diffusion and construct global smooth solutions by choosing a class of special initial data $(u_0,v_0,θ_0)$ whose $L^2$ norm can be arbitrarily large, and improve the previous results in [1,2].
Keywords: Tropical climate model; zero thermal diffusion; global large solution; Sobolev spaces.